a2=√3/2
a3=-3/2
q=a3/a2
q=-3/2:√3/2=-3/2 * 2/√3 = -3/√3 = -3*√3/√3*√3=-3√3/3=-√3
a1*q=a2
a1=a2/q
a1=√3/2:(-√3)=√3/2 * (-1/√3) = -1/2
odp:
a1=-1/2
a2²=a1*a3
a1=a2²:a3
a1=3/4:(-3/2)=-1/4*2=-1/2
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
a2=√3/2
a3=-3/2
q=a3/a2
q=-3/2:√3/2=-3/2 * 2/√3 = -3/√3 = -3*√3/√3*√3=-3√3/3=-√3
a1*q=a2
a1=a2/q
a1=√3/2:(-√3)=√3/2 * (-1/√3) = -1/2
odp:
a1=-1/2
a2²=a1*a3
a1=a2²:a3
a1=3/4:(-3/2)=-1/4*2=-1/2